The Influence of Customer Perception About Profit Sharing, Promotion and Quality of Service on The Customer Interest in Saving at BRI Syari'ah Branch Purwokerto - Akhmad Faozan (Ijtimā iyya Journal of Muslim Society Research, 2022)
Public perceptions and attitudes towards bank interest and profit-sharing systems vary widely. Some people in Indonesia accept and reject bank interest, but some others accept the profit-sharing system while still receiving interest. These diverse attitudes provide an interesting nuance as an illustration of people's perceptions and attitudes towards bank interest and profit sharing. This study aims to examine the effect of customer perceptions of profit sharing on the intention to save, examine the effect of customer perceptions of promotions on interest in saving, examine the effect of customer perceptions of service quality on interest in saving and examine the effect of profit sharing, promotion and service quality as a whole simultaneous on customers' interest in saving. The author distributes questionnaires to customers funding at BRI Syariah Purwokerto Branch. Respondents who became the sample in this study were 100 customers. The technique of determining the sample using the technique puposive sampling. The data analysis method is carried out by carrying out several tests, namely validity, reliability, classic assumptions and hypothesis testing which includes the t test and f test. The results of this study indicate that: 1) customer perceptions of profit sharing affect the customer's intention to save as indicated by the t-count value which is greater than t-table where the t-count value is 2.351 and the t-table value is 1.984, 2). Customer perceptions about promotions have no effect on the intention to save as indicated by the t-count value which is smaller than the t-table where the t-count value is 0.416 and the t-table value is 1.984, 3). Customer perceptions of service quality have an effect on customers' interest in saving as indicated by the t-count value which is greater than t-table where the t-count value is 2.102 and the t-table value is 1.984, and 4). customer perceptions about profit sharing, promotions and service quality simultaneously effect on the interest in saving as indicated by the results of the calculation of the f test where the value of f calculate 4.382 which is greater than f table 2.70.